2012
DOI: 10.1177/1471301212438290
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the use of music therapy in the context of Alzheimer's disease: A report of a French expert group

Abstract: Psychosocial interventions, such as music therapy, can contribute to maintain or rehabilitate functional cognitive and sensory abilities, as well as emotional and social skills and to reduce the severity of some behavioural disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 60 publications
1
41
0
7
Order By: Relevance
“…Long-term meditation practice has also been associated with cortical thickening and increased grey matter volume in brain regions involved in attentional performance, memory, sensory processing, and interoception [149151], apparently offsetting typical age-related cortical thinning and grey matter loss [149, 151, 152]. While data regarding CNS changes with music are more limited, neuroimaging studies likewise suggest that music therapy, including ML, activates pathways in brain areas involved in emotional reward and regulation, attention, memory, and other associated functions, including the prefrontal cortex, insular and cingulate cortex, hippocampus, and amygdala [63, 66, 143]. …”
Section: Discussionmentioning
confidence: 99%
“…Long-term meditation practice has also been associated with cortical thickening and increased grey matter volume in brain regions involved in attentional performance, memory, sensory processing, and interoception [149151], apparently offsetting typical age-related cortical thinning and grey matter loss [149, 151, 152]. While data regarding CNS changes with music are more limited, neuroimaging studies likewise suggest that music therapy, including ML, activates pathways in brain areas involved in emotional reward and regulation, attention, memory, and other associated functions, including the prefrontal cortex, insular and cingulate cortex, hippocampus, and amygdala [63, 66, 143]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms by which music therapy works are not well understood, the most commonly accepted theories are through neurologic, psychological, behavioral, and physiologic pathways. 180,181 The practice of music therapy in North American is regulated by some US states ( Table 2).…”
Section: Music Therapymentioning
confidence: 99%
“…These results confirm the findings observed by Thompson et al57 Chu et al55 observed that group music intervention is a non-invasive and inexpensive therapy that reduces depression in aging adults and delays the deterioration of cognitive functions, particularly short-term recall among aging adults with mild and moderate dementia. Previous studies have focused on aging adults with dementia 12,25,26,3133. Our study is the first to investigate the effects of music intervention on cognitive function and depression in healthy residents in a senior citizen apartment.…”
Section: Discussionmentioning
confidence: 97%